Using Myriophyllum aquaticum (Vell.) Verdc. to remove heavy metals from contaminated water: Better dead or alive?. (1st May 2018) - Colzi, Ilaria; Lastrucci, Lorenzo; Rangoni, Mattia; Coppi, Andrea; Gonnelli, Cristina
Abstract: This study aimed to investigate the potential of the invasive macrophyte Myriophyllum aquaticum to remove heavy metals. The elements tested were Cd, Cr, Ni, and Zn, in single-metal trials, and experiments were performed with both the living and dead biomass of the plant. In respect of metal removal by living plants, the element that was removed the most was Zn, though Cd showed the highest concentration in plant shoots. The metal negative effect on plant growth was, therefore, more important than the level of metal concentration in plant tissue in determining the removal percentages. All the metals were mostly accumulated in the roots, where a considerable fraction of the element was simply adsorbed to root cell wall, except in the case of Cr. In shoots, the fraction of the adsorbed metal was extremely low in respect to roots, thereby implying a lower apoplastic binding capacity. As regards a possible use of the dead biomass for metal removal, we proposed the generation of a hybrid biosorbent enclosing the dried and grounded plant biomass in cotton bags to improve its handling and its adsorption capacity, in view of a valid alternative to reduce the problems of packed beds. Cadmium—and especially Zn—were the elements removed most efficiently with respect to the other metals. On comparing the removal percentages of the living biomass and the hybrid biosorbent, our data deposed in favour of the use of M. aquaticum as dead biomass for a possible application of this invasive macrophyte in the biological treatment of metal-contaminated water. Our findings may be beneficial to metal removal application accompanying wetland management, devising a possible use of M. aquaticum waste material after its removal from the invaded habitats. Highlights: Myriophyllum aquaticum was tested for the removal of Cd, Cr, Ni and Zn from water. Both living and dried plant biomasses were used for the experiments. Cadmium was the most accumulated in plant shoots and Zn the most removed. A hybrid biosorbent was developed using dead biomass and cotton fiber. The biosorption was highly effective in removing Cd and especially Zn.